MENGEMBANGKAN POTENSI JAMU MELALUI DESA WISATA JAMU DAN PANGAN KREATIF - Andini, Thathit Manon; Alifatin, Aini; Kurniawati, Dini; Nurhayatin, Nurhayatin; Suharso, Wildan; Thoyyibah, Anisatu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
Abstract: Karangrejo Village, Kromengan Subdistrict, Malang Regency, which is well known as a producer of herbal medicine know as ‘Jamu Gendong’ since 1983 with 150 sellers of jamu Gendong incorporated in the Jamu Gendong Association of Karangrejo village, is still carrying out traditional production and marketing processes by carrying it around and going out of the area. In line with Permenkes No 3/2010 policy on herbal medicine scientification in research based on health services, which aims to increase the use of herbal medicine in health services through scientific research, as well as marketing activities that are very time-consuming and low production development, making Karangrejo village together with UMM Community Service Team, sparked Karangrejo Village as a Herbal Tourism and Creative Food Village. The approach method is aimed at 3 (three) main groups supporting the village economy, namely Village-owned business entity (BUMDes), tourism aware groups (POKDARWIS) and herbal medicine group POKJAMU, which include: Community facilitation models in the form of training and enhancing the quality of partner resources related to strengthening and fostering the structure and function of the organization, in the form of setting Vision, Mission, Logo, AD / ART to short and long term work plans. While assistance in the framework of production processing, packaging, marketing, diversification of processed products is carried out in order to improve production quality. Cooperation with the Department of food crop, Hortikultura and plantations in the procurement of ginger and turmeric seeds is aimed at reforesting the medicinal education tourism area. The construction of the Archway, the zero point tourism monuments and publications are carried out through weblogs, online and print publications.